2016
DOI: 10.3390/met6030049
|View full text |Cite
|
Sign up to set email alerts
|

The Hot Deformation Activation Energy of 7050 Aluminum Alloy under Three Different Deformation Modes

Abstract: Abstract:In this study, the hot deformation activation energy values of 7050-T7451 aluminum alloy, calculated with two different methods under three deformation modes, were compared. The results showed that the hot deformation activation energy values obtained with the classical constitutive equation are nearly equivalent under the hot tensile, compression, and shear-compression deformation modes. Average values exhibited an obvious increase when calculated with the modified constitutive equation because it ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 18 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…Elevated temperature response of aluminum alloys is of interest for estimation of critical force levels for any application-oriented loading event as well as for metal forming at elevated temperatures [21,22,[28][29][30][31][32][33]. Many researchers utilized hot compression, tension, and torsion experiments to obtain flow curves at elevated temperatures [21,22,[28][29][30][31][32][33]. Instability phenomena during tensile testing are a barrier toward constitutive analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated temperature response of aluminum alloys is of interest for estimation of critical force levels for any application-oriented loading event as well as for metal forming at elevated temperatures [21,22,[28][29][30][31][32][33]. Many researchers utilized hot compression, tension, and torsion experiments to obtain flow curves at elevated temperatures [21,22,[28][29][30][31][32][33]. Instability phenomena during tensile testing are a barrier toward constitutive analysis.…”
Section: Introductionmentioning
confidence: 99%
“…More generally, the deformation activation energy is an important physical and kinetic parameter indicating plastic deformability and qualitatively reflects the energy barrier to dislocation motion for metals, alloys as well as metal matrix nanocomposites (Li et al ., 2016; Wang et al ., 2017). In this end, it can be rationalised to expect a higher value of this energy signifying higher dragging forces to the movement of the dislocations in hot deformation processes (Sang et al ., 2016). To describe the relationship of flow stress on deformation temperature and strain rate, there are three typical constitutive equations namely the power, the exponential and the hyperbolic sine law.…”
Section: Resultsmentioning
confidence: 99%
“…ε is the strain rate (s −1 ), and T is the absolute deformation temperature (K). Equation (4) is obtained by taking the logarithm twice on both sides of Equation (2).…”
Section: Srx Kinetic Model Of 5754 Aluminium Alloymentioning
confidence: 99%
“…The heating process used to form materials is of remarkable importance, as it affects the quality of the products [1,2]. However, previous studies have shown that complex metallurgical structural changes that occurred during multi-pass hot rolling and hot compression processes resulted from competing work hardening and softening mechanisms [3,4].…”
Section: Introductionmentioning
confidence: 99%